Association of post-thrombotic syndrome with metabolic syndrome and inflammation - a systematic review - Alturky, Sara; Ashfaq, Yusuf; Elhance, Ajit; Barney, Megan; Wadiwala, Ishaq; Hunter, Anna K.; Nguyen, Khanh P. (Frontiers in Immunology, 2025)
IntroductionPost-thrombotic syndrome (PTS) is a chronic complication of deep vein thrombosis (DVT). Given its impact on vascular health, understanding risk factors for the development of PTS, as well as conditions such as metabolic syndrome that may contribute to vascular inflammation, is crucial. Metabolic syndrome is a constellation of factors that increase cardiovascular disease risk, insulin resistance, diabetes mellitus (DM), and cerebrovascular disease. Despite the established connection between metabolic syndrome and venous thromboembolism (VTE), the association between metabolic syndrome and PTS has yet to be explored.MethodsA literature search identified studies regarding PTS and metabolic syndrome and the individual components of metabolic syndrome. A specialist performed the search, and studies were identified through PubMed, Ovid Medline, and Cochrane in accordance with PRISMA guidelines. Search terms included “post-thrombotic syndrome” and “metabolic syndrome” as well as “obesity,” “hyperglycemia,” “hypertension,” “dyslipidemia,” and “insulin resistance.” Two people independently screened articles and consolidated differences. Abstract-only studies, review articles, case studies, and conference abstracts were excluded. Case reports, literature reviews, and studies not discussing PTS were excluded. Prospective cohort, retrospective cohort, and case-control studies were included. All English-based studies that met inclusion criteria published before January 3rd, 2024, were included.Results281 articles were initially identified. After abstract and title screening, 16 articles underwent full-text review. Of the 16 articles that underwent review, nine were included in the final analysis. Among the selected articles, eight out of nine mentioned obesity as a risk factor for developing PTS, making it the most common component mentioned. Hypertension, diabetes mellitus, hyperlipidemia, and low high-density lipoprotein (HDL) followed in prevalence. There was no noted difference between inflammatory markers in patients with and without PTS.ConclusionMetabolic syndrome and its components, individually and in association with PTS, are not commonly examined. Eight articles examined the association of obesity with the development of PTS. This review identified a strong association between obesity, particularly abdominal or visceral obesity, and the development of PTS. While the association between PTS and VTE is established, further research is needed to identify the role of metabolic syndrome in the development of PTS.